Micaceous Soil Strength and Permeability Improvement Induced by Microbacteria from Vegetable Waste - Omar R.C.; Roslan R.; Baharuddin I.N.Z.; Hanafiah M.I.M. (Institute of Physics Publishing, 2023)
Bacteriology; Curing; Grouting; Mortar; Slope stability; Soils; Vegetables; Bacillus pasteurii; Bacillus Subtilis; Green technology; Optimum value; Permeability improvements; Residual soil; Stability of the slopes; Vegetable wastes; Engineering research